Evaluation of effective doses in CT simulation using CTDIw calculation - Sanklaa, Khemipa; Sanghangthum, Taweap; Chongsan, Thanaphat (Journal of Associated Medical Sciences, 2017)
Background: Computed Tomography (CT) simulator is used for primary imaging in Department of Radiation Therapy. Although it is also the leading standard of treatment planning since it directly measures electron densities needed for dosage computation, it is known to deliver more radiation dose to patients. Objectives: The purpose of this study is to determine the effective dose for cancer patients undergoing the CT simulator. Materials and methods: An ionization chamber was used to measure CTDIair in CT simulator (Siemens, Somatom Definition AS, Germany). Measurement of CTDIw was done by placing the Pencil Ionization Chamber (Radcal, USA, SN:05-0340) in PMMA head and body phantoms to measure CTDI100 for the head and abdomen region, respectively. Twenty cases of head, thorax, and pelvic cancer patients were recorded. CTDIvol, DLP, scan length, kV, mAs, pitch, and rotation time parameters were collected in each patient for CTDIw dose calculation to obtain the effective dose. Results: Dose index in air (CTDIair) was 8.84 mGy and CTDIw in PMMA head and body phantom were 16.67 and 10.33 mGy, respectively. Effective doses in head, thorax, and abdomen cases were shown to be 2.20±0.06, 5.01±1.09, 6.90±1.23 mSv, respectively. Conclusion: Effective doses were different in each region. Although, they were less than recommended, it should still be taken into consideration. Protocol optimization in CT simulator should be considered about pitch, scan length, slice thickness and mAs while image quality would be accepted.